Democratising science - Miquel Domènech (Revue d'anthropologie des connaissances)
With knowledge societies, the role of expert knowledge has grown to cover all areas of social life. When it affects deliberative processes and political decision-making, this role questions the quality and nature of contemporary democratic systems owing to the distance it sets up between citizenship and public matters. The demand for a democratisation of science has been one of the most frequently proposed responses to this problem in science and technology studies since the start of the 21st century. This challenge is still on-going, mainly due to the fact that it has been addressed through conceptions of science and politics that have turned it into a difficult-to-achieve if not impossible objective. While recognising that the relevance of this challenge has never been doubted, this article puts forward a number of suggestions as to what topics and questions might be dealt with for this project to democratise science to make sense for our discipline.